An Analytical Approach to the Inventory Management System of Turkish Technic - Karagöl, Belma Nüvit; Çöpürkaya, Derya; Kodaz, Kubilay; Ünek, Simge; AKTİN, AYŞE TÜLİN (My University, 2018)
Time, which constitutes an important limitation in a company’s operations, is a factor that affects the supply chain processes and cash flow. Another element that has an influence on cash flow is customer satisfaction. Sector leaders are mostly companies having high customer service levels. Moreover, there exists a strong bond between customer satisfaction and inventory. This study aims to propose an analytical approach to the inventory management policy of a company operating in the aviation industry. Founded in 2006, Turkish Technic has been established to support Turkish Airlines and other aviation companies in their maintenance, repair and overhaul (MRO) services. Aircraft are served in the hangars located at Istanbul Atatürk and Sabiha Gökçen Airports. As a result of their high safety and quality standards, Turkish Technic has become the leader MRO company in the region. Being an exemplary model in its sector, the company relies on the effective management of the diverse parts held in stock both as an indicator of the existence of a robust inventory system, and for a sustainable reputation. Since Turkish Technic holds a variety of parts, initially an ABC analysis will be performed in selecting the most critical ones. Using the past data acquired from the company and Arena Input Analyzer, demand distributions will be obtained and demand quantities for 2018 will be forecasted for each selected part. In the next step, optimum order sizes, safety stock levels, and reorder points of these parts will be calculated. Mathematical modelling and Excel will be used to determine these quantities. The aim is to minimize inventory holding costs, while meeting a preset cycle service level (CSL). The proposed model will be solved using GAMS/CPLEX software. Scenario analysis will be performed to observe and compare the effects of different CSLs on the behaviour of the company’s inventory system.